Peran Kepemimpinan Kepala Desa Dalam Pemberian Pelayanan Publik Dan Tantangannya Pada Era Revolusi Industri 4.0 (Desa Gandasuli Kabupaten Halmahera Selatan) - Ali, Risman; Marwan, Marwan; Rajak, Adnan; Thahrim, Muhammad; Taslim, Fadli Ali (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2022)
The purpose of this study was to determine the leadership role of the village head in providing public services and the challenges in the Industrial Revolution 4.0 era in Gandasuli Village. Researchers use indicators of motivators, facilitators, and mobilizers to determine the leadership role of the village head in providing public services, while the challenge is that researchers use indicators of support, capacity, and value. This research uses a descriptive qualitative method, and the data analysis used is an interactive model starting from reduction, data presentation, and verification/conclusion. The results of this study indicate that the leadership role of the village head in providing public services with the roles of motivator, facilitator, and mobilizer has not been maximized. Meanwhile, the challenge of providing public services in Gandasuli Village in the era of the Industrial Revolution 4.0 was sufficient support from the local government, but in terms of capacity, there are not yet qualified human resources. The value will be that there will be benefits for service providers and service recipients in Gandasuli Village when implementing a digital-based service system.